PENGGUNAAN GERGAJI RANTAI PADA PENEBANGAN JATI DAN DAMPAKNYA TERHADAP KEBISINGAN DAN BEBAN KERJA - Soenarno Soenarno; Maman Mansyur Idris (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
It is obvious that the use. of chainsaw in teak felling has some advantages not only in increasing productivity but also in reducing felling defects.Nevertheless, uaing chainsaw in teak felling has also created a lot of inconveniences to forest worker. Thess inclu de the distruction of physical climatic conditions and heavier phsycological stress of forest workers due to combined physical workload, noise and fear of accident effects.Base on the above reasons research on noise and forest workers' workstress. is needed. this research is intended to determine a better method of felling technique in the efforts of controlling noise to provide a more favourable conditions for the workers. This research was carried out in Saradan Forest District, East Java.The results of the research reveal that both noise and the workers' streu rate occurinf at teak felling ia higher than at acceptable by the